The Records Management (RM) Capabilities of Lecturers at Midlands State University (MSU), Zimbabwe - Chitima, Simbarashe Shadreck; Dewah, Peterson (Mousaion: South African Journal of Information Studies, 2023)
Records bear evidence of business transactions and decisions undertaken by an organisation. Good records management enables the smooth flow, efficient and effective conduct of university business. University lecturers create different types of records in the course of discharging their responsibilities. These include research and publications, student teaching, continuous assessment, and examination. However, very little is known about the extent to which lecturers are able to properly manage the records they create. There have been three recorded cases of lecturers at Midlands State University (MSU) who lost examination and continuous assessment records, and this led to their dismissal. This study examined the capabilities of university lecturers in managing the records they create. The objectives of the study were to ascertain the records management background of lecturers and to examine their capability to perform records management. This study was grounded on the interpretive paradigm and employed qualitative research approaches where convenience sampling was used. The sample of the study involved 23 lecturers and one staff member from the Central Records section at MSU. The study found that participating lecturers lacked records management knowledge, and all of them did not follow any records management system for paper-based records management. Lecturers managed coursework and examination records through the Changamire Marks Management System. Some electronic records were kept in lecturers’ e-mails and personal laptops. The study established that records were susceptible to loss due to lecturers’ lack of knowledge, negative attitudes, conflicts between non-teaching and teaching staff, and lack of suitable records management infrastructure. The study concluded that most lecturers who participated in the study were dismal performers of records management; hence, records are more susceptible to loss. This study provides a step by step systems approach that universities, such as MSU, can employ to effectively manage records created by academic staff.